Influence of carbohydrate on the microparticulation process of whey proteins: structural modifications and indicators of the Maillard Reaction - Igor L. de Paula; Natalia C. Mesa; Alan F. Wolfschoon-Pombo; Uwe Schwarzenbolz; Thomas Henle; Ítalo T. Perrone; Luiz Fernando C. de Oliveira; Rodrigo Stephani (International Dairy Journal, 2026)

Sexually dimorphic effects of prenatal diazepam exposure on respiratory control and the monoaminergic system of neonate and young rats - Carlos Aparecido da Silva Junior; Luís Gustavo A. Patrone; Vivian Biancardi; Heloísa H. Vilela-Costa; Danuzia A. Marques; Caroline Cristina-Silva; Kaoma Stephani da Costa Silva; Kênia C. Bícego; Raphael E. Szawka; Luciane H. Gargaglioni (Pflügers Archiv - European Journal of Physiology, 2022)

Considerations for management strategy evaluation for small pelagic fishes - Margaret C. Siple; Laura E. Koehn; Kelli F. Johnson; André E. Punt; T. Mariella Canales; Piera Carpi; Carryn L. de Moor; José A. A. De Oliveira; Jin Gao; Nis S. Jacobsen; Mimi E. Lam; Roberto Licandeo; et al. (Fish and Fisheries, 2021)
Management strategy evaluation (MSE) is the state‐of‐the‐art approach for testing and comparing management strategies in a way that accounts for multiple sources of uncertainty (e.g. monitoring, estimation, and implementation). Management strategy evaluation can help identify management strategies that are robust to uncertainty about the life history of the target species and its relationship to other species in the food web. Small pelagic fish (e.g. anchovy, herring and sardine) fulfil an important ecological role in marine food webs and present challenges to the use of MSE and other simulation‐based evaluation approaches. This is due to considerable stochastic variation in their ecology and life history, which leads to substantial observation and process uncertainty. Here, we summarize the current state of MSE for small pelagic fishes worldwide. We leverage expert input from ecologists and modellers to draw attention to sources of process and observation uncertainty for small pelagic species, providing examples from geographical regions where these species are ecologically, economically and culturally important. Temporal variation in recruitment and other life‐history rates, spatial structure and movement, and species interactions are key considerations for small pelagic fishes. We discuss tools for building these into the MSE process, with examples from existing fisheries. We argue that model complexity should be informed by management priorities and whether ecosystem information will be used to generate dynamics or to inform reference points. We recommend that our list of considerations be used in the initial phases of the MSE process for small pelagic fishes or to build complexity on existing single‐species models.

The Toxicology Investigators Consortium 2020 Annual Report - Meghan B. Spyres; Kim Aldy; Lynn A Farrugia; A. Min Kang; Jennifer S. Love; Sharan L. Campleman; Shao Li; Alexandra Amaducci; Evan Schwarz; Paul M. Wax; Jeffery Brent; J. Acciani; et al. (Journal of Medical Toxicology, 2021)

Progress on Implementing Ecosystem-Based Fisheries Management in the United States Through the Use of Ecosystem Models and Analysis - Howard Townsend; Chris J. Harvey; Yvonne deReynier; Dawn Davis; Stephani G. Zador; Sarah Gaichas; Mariska Weijerman; Elliott L. Hazen; Isaac C. Kaplan (Frontiers in Marine Science, 2019)

Comparing Apples to Oranges: Common Trends and Thresholds in Anthropogenic and Environmental Pressures across Multiple Marine Ecosystems - Jamie C. Tam; Jason S. Link; Scott I. Large; Kelly Andrews; Kevin D. Friedland; Jamison Gove; Elliott Hazen; Kirstin Holsman; Mandy Karnauskas; Jameal F. Samhouri; Rebecca Shuford; Nick Tomilieri; et al. (Frontiers in Marine Science, 2017)

Puffins reveal contrasting relationships between forage fish and ocean climate in the North Pacific - William J. Sydeman; John F. Piatt; Sarah Ann Thompson; Marisol García‐Reyes; Scott A. Hatch; Mayumi L. Arimitsu; Leslie Slater; Jeffrey C. Williams; Nora A. Rojek; Stephani G. Zador; Heather M. Renner (Fisheries Oceanography, 2017)
Long‐term studies of predator food habits (i.e., ‘predator‐based sampling’) are useful for identifying patterns of spatial and temporal variability of forage nekton in marine ecosystems. We investigated temporal changes in forage fish availability and relationships to ocean climate by analyzing diet composition of three puffin species (horned puffin Fratercula corniculata , tufted puffin Fratercula cirrhata , and rhinoceros auklet Cerorhinca monocerata ) from five sites in the North Pacific from 1978–2012. Dominant forage species included squids and hexagrammids in the western Aleutians, gadids and Pacific sand lance ( Ammodytes personatus ) in the eastern Aleutians and western Gulf of Alaska (GoA), and sand lance and capelin ( Mallotus villosus ) in the northern and eastern GoA. Interannual fluctuations in forage availability dominated variability in the western Aleutians, whereas lower‐frequency shifts in forage fish availability dominated elsewhere. We produced regional multivariate indicators of sand lance, capelin, and age‐0 gadid availability by combining data across species and sites using Principal Component Analysis, and related these indices to environmental factors including sea level pressure ( SPL ), winds, and sea surface temperature ( SST ). There was coherence in the availability of sand lance and capelin across the study area. Sand lance availability increased linearly with environmental conditions leading to warmer ocean temperatures, whereas capelin availability increased in a non‐linear manner when environmental changes led to lower ocean temperatures. Long‐term studies of puffin diet composition appear to be a promising tool for understanding the availability of these difficult‐to‐survey forage nekton in remote regions of the North Pacific.

Functional neuroanatomy of the insular lobe - C. Stephani; G. Fernandez-Baca Vaca; R. Maciunas; M. Koubeissi; H. O. Lüders (Brain Structure and Function, 2011)

Association Study of TRPC4 as a Candidate Gene for Generalized Epilepsy with Photosensitivity - Sarah von Spiczak; Hiltrud Muhle; Ingo Helbig; Carolien G. F. de Kovel; Jochen Hampe; Verena Gaus; Bobby P. C. Koeleman; Dick Lindhout; Stefan Schreiber; Thomas Sander; Ulrich Stephani (NeuroMolecular Medicine, 2010)

Survival rate, abundance, and residency of long‐finned pilot whales in the Strait of Gibraltar - P. Verborgh; R. De Stephanis; S. Pérez; Y. Jaget; C. Barbraud; C. Guinet (Marine Mammal Science, 2009)
Long‐finned pilot whales in the Strait of Gibraltar are distributed over the main shipping routes. This exposes them to risks of collisions and probable acoustic and physical disturbance. This species is also the target of whale‐watching operations. The aim of this study was to estimate the annual population size, survival rate, and population growth rate of pilot whales occurring in the Strait and their inter‐annual variation using photo‐identification. A robust design was used to estimate all three parameters. A total of 10,784 individual pilot whale fins were photographed and analyzed. The population size estimation in summer ranged from a low of 147 individuals in 1999 to a high of 265 individuals in 2003. The annual population growth rate was estimated from mark recapture models to be 5.5%. The survival rate of adults was estimated at 0.982 (95% CI: 0.955–0.993). The same individuals have been observed between years. This suggests that this population is resident in the Strait, at least during summer. This study provides baseline knowledge prior to a predicted increase in shipping traffic throughout the main foraging area due to the opening in 2007 of a major shipping harbor along the Moroccan coast of the Strait.

Long-term social structure of long-finned pilot whales (Globicephala melas) in the Strait of Gibraltar - R. de Stephanis; P. Verborgh; S. Pérez; R. Esteban; L. Minvielle-Sebastia; C. Guinet (acta ethologica, 2008)

Diet of the social groups of long-finned pilot whales (Globicephala melas) in the Strait of Gibraltar - R. de Stephanis; S. García-Tíscar; P. Verborgh; R. Esteban-Pavo; S. Pérez; L. Minvielle-Sebastia; C. Guinet (Marine Biology, 2008)